Effects of fire on soil carbon and nitrogen in a Mediterranean oak forest of Algeria (Plant and Soil, 1987)
The effects of wildfire on the dynamics of pH, organic C, total and mineral N and in vitro C and N mineralization were investigated in the soil under oak (Quercus suber L.) trees. Soil samples were taken from 5 to 21 months subsequent to the fire. The pH increased sharply in the burned surface soil (0-5 cm) taken 5 months after the fire and dropped only by half a unit over 14 to 21 months. However, at greater depth (5-15 cm), the burned soil was more acidic than the adjacent unburned soil up to 9 months following the fire, and thereafter its pH rose only slightly above that of the unburned soil. There were sharp rises in the concentration of organic C, total and mineral N in addition to in vitro mineralization activities in the burned surface soil collected 5 months after the fire; these dropped off in the subsequent samples approaching or falling below the values obtained in the unburned surface soil after 21 months. At a depth of 5-15 cm only slight or no increases over unburned soil were evident.